Analysis of Risk Factors of Husband's Readiness and Involvement in Accompanying Wives in Childbirth: An Observational Study in Bengkulu City, Indonesia - Murwati; Tita Septi Handayani; Ida Samidah (HM Publisher, 2024)
The husband's role in assisting wives in childbirth has a significant impact on the birth experience and the health of the mother and baby. This study aims to analyze the risk factors that influence the role of husbands in accompanying their wives in childbirth in Bengkulu City, Indonesia. Analytical observational research was conducted on 200 married couples who gave birth in health facilities in Bengkulu City. Data was collected through questionnaires, interviews, and participant observation. Data analysis was carried out using logistic regression to identify risk factors related to the husband's role in accompanying wives in childbirth. The results showed that significant risk factors related to the husband's role in assisting wives in childbirth were the husband's education level (OR = 2.34; 95% CI: 1.21-4.53), the husband's knowledge about childbirth (OR = 3.12; 95% CI: 1.68-5.79), husband's attitude towards the role of mentoring (OR = 2.87; 95% CI: 1.45-5.68), social support from the family (OR = 1.98; 95% CI: 1.05-3.73), and previous birth experience (OR = 2.15; 95% CI: 1.12-4.14). This research identifies several risk factors that influence the husband's role in assisting wives in childbirth. Interventions aimed at increasing husbands' education, knowledge, and positive attitudes towards the role of companionship, as well as strengthening social support from the family, can increase husbands' involvement in the childbirth process.